Development of Alphabetic Cards as A Learning Medium for the Community Learning Activity Center Community - Pinontoan, Marien; Wullur, Mozes Markus; Dumanaw, Ronny G.; Rahmat, Abdul (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
The development of the Out-of-School Education sector has a strategic role in improving the quality of human resources. Learning media in alphabet cards is needed to increase students' motivation and learning achievement in reading learning, which are used as a learning resource to develop learning models while playing for students. This research aims to determine and test the effectiveness of implementing the development of the learning process for reading while playing through alphabet card learning media for residents learning literacy in PKBM North Sulawesi Province. This research uses the